Evaluasi Efektifitas Penggunaan Uterotonika Misoprostol pada Induksi Persalinan Kehamilan Postterm - Eka Nur Fatmawati; Ratna Mildawati; Yuneka Saristiana; Fendy Prasetyawan; Faisal Akhmal Muslikh (Universitas Ngudi Waluyo, 2024)
Postterm pregnancy, namely pregnancy that reaches 42 weeks or exceeds 294 days which requires appropriate treatment and there are indications of labor induction. The principle of labor management in postterm pregnancy is the fulfillment of the requirements for induction of labor. The pharmacological induction method uses the uterotonic drug misoprostol. This research aims to evaluate and analyze the cost effectiveness of using the uterotonic misoprostol in labor induction of postterm pregnancies. This research method is descriptive observation using a cross-sectional research design from a hospital perspective. Retrospective data collection method. Evaluation of the effectiveness of using the uterotonic misoprostol with percentages. The results of this study show the pattern of use of misoprostol uterotonics (73.5%), the use of uterotonics is in accordance with hospital guidelines (96%), the effectiveness of using uterotonics is successful in preventing bleeding (57.4%). And analysis of the cost effectiveness of using misoprostol and oxytocin in labor induction at RSUD dr. Sayidiman Magetan can conclude that misoprostol uterotonic is more effective with a percentage value of 60%. Abstrak Kehamilan postterm, yaitu kehamilan yang mencapai 42 minggu atau melewati 294 hari yang memerlukan penanganan tepat dan muncul indikasi dilaksanakan induksi persalinan. Prinsip penatalaksanaan persalinan pada kehamilan postterm adalah terpenuhinya syarat-syarat melakukan induksi persalinan. Metode induksi farmakologis menggunakan obat uterotonika misoprostol. Pelitian ini bertujuan untuk mengevaluasi dan analisis efektifitas biaya penggunaan uterotonika misoprostol pada induksi persalinan kehamilan postterm. Metode penelitian ini observasi deskriptif dengan menggunakan rancangan penelitian cross sectional menurut perspektif rumah sakit. Metode pengambilan data secara retrospektif. Evaluasi efektifitas penggunaan uterotonika misoprostol dengan persentase. Hasil penelitian ini menunjukkan pola penggunaan uterotonika misoprostol (73,5%), penggunaan uterotonika sudah sesuai dengan guideline rumah sakit (96%), efektifitas penggunaan uterotonika berhasil mencegah perdarahan (57,4%). Dan analisis efektifitas biaya penggunaan misoprostol dan oksitosin pada induksi persalinan di RSUD dr. Sayidiman Magetan dapat disimpulkan uterotonika misoprostol lebih effective dengan nilai persentase 60 %.